Missing the mark(ers): circulating endothelial cells and endothelial-derived extracellular vesicles are elevated in sickle cell disease plasma - Beckman, Joan D.; Zhang, Ping; Nguyen, Julia; Hebbel, Robert P.; Vercellotti, Gregory M.; Belcher, John D. (Frontiers in Immunology, 2024)
Sickle cell disease (SCD) is a devastating hemolytic disease, marked by recurring bouts of painful vaso-occlusion, leading to tissue damage from ischemia/reperfusion pathophysiology. Central to this process are oxidative stress, endothelial cell activation, inflammation, and vascular dysfunction. The endothelium exhibits a pro-inflammatory, pro-coagulant, and enhanced permeability phenotype. We used flow cytometry to enumerate circulating endothelial cells (CECs, CD31+/CD45-/CD146+) in SCD and normal healthy control blood samples. Furthermore, we assessed CEC subtypes, including circulating endothelial progenitor cells (EPCs, CD31+/CD45-/CD146+/CD133+) and mature CECs (mCECs, CD31+/CD45-/CD146+/CD133-) with mCECs further subdivided into resting CECs (rCECs, VCAM-1-) and activated CECs (aCECs, VCAM-1+). As compared to healthy controls, total CECs and mCECs were elevated in SCD blood as compared to healthy control blood. Using the same markers along with size-based gating, we also used flow cytometry to enumerate endothelial-derived extracellular vesicles (EEVs) in plasma. We assessed EEV subtypes based on VCAM-1 expression, including activated EEVs (aEEVs, CD31+/CD45-/CD146+/CD133-/VCAM-1+) and resting EEVs (rEEVs, VCAM-1 negative), presumably derived from activated and resting endothelial cells, respectively. aEEVs were elevated in SCD patient plasma as compared to healthy controls. Importantly, in SCD patients, total EEVs and aEEVs were increased during self-reported pain crisis as compared to steady state. Plasma markers of endothelial cell activation including soluble E-selectin, P-selectin, VCAM-1, and ICAM-1 were elevated in SCD plasma. These data highlight strategies to detect SCD-related endothelial cell activation and demonstrate that endothelial cell activation markers may be useful to evaluate curative and non-curative therapies in SCD patients.